2013
DOI: 10.1002/jgra.50457
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of field‐aligned current formation in magnetic reconnection

Abstract: [1] Satellite observations provide strong evidence for the generation of significant field-aligned currents (FACs) during magnetic reconnection. Reconnection of antiparallel magnetic field does not generate FACs in magnetohydrodynamics (MHD) due to coplanarity in MHD shocks. However, a guide magnetic field and a sheared velocity component are almost always present at the magnetopause and their absence is a singular case. It is illustrated that the presence of these noncoplanar fields requires FACs. Contrary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Examination of conditional PDFs in the MHD runs (not shown), reveals that, while there may be some association between strong currents and highly-aligned σ jb , the association tends to be stronger in HMHD. Evidence has also been found that the inclusion of the Hall term can generate magnetic field-aligned currents in laminar reconnection [79,80]. the Earth's magnetotail.…”
Section: B Behavior In Real Spacementioning
confidence: 99%
“…Examination of conditional PDFs in the MHD runs (not shown), reveals that, while there may be some association between strong currents and highly-aligned σ jb , the association tends to be stronger in HMHD. Evidence has also been found that the inclusion of the Hall term can generate magnetic field-aligned currents in laminar reconnection [79,80]. the Earth's magnetotail.…”
Section: B Behavior In Real Spacementioning
confidence: 99%
“…The basic mechanism is already present in two-dimensional reconnection [La Belle-Hamer et al, 1995]. It is important to realize that the accumulation of B y flux generates a significant field-aligned current [Ma and Otto, 2013], which in turn can cause reconnection. For instance, the magenta and orange lines in Figure 2 show a moderate field-aligned potential difference (see the Figure 6 (right)).…”
Section: Overall Dynamicsmentioning
confidence: 99%
“…In the presence of plasma flow, magnetic reconnection is associated with the generation of field‐aligned currents (FACs), which play a critical role in the coupling between the magnetosphere and ionosphere [ Ma and Otto , ]. The generation is basically one‐dimensional [ Lin and Lee , ] and has also been demonstrated in two‐dimensional geometry [ La Belle‐Hamer et al , ].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Field-aligned electric potential difference at t = 20, 48, 90, 104, and 144 for the reference case in a cut at z = 1 close to the equatorial plane. [Ma and Otto, 2013]. The generation is basically one-dimensional [Lin and Lee, 1993] and has also been demonstrated in two-dimensional geometry [La Belle-Hamer et al, 1995].…”
Section: Overall Dynamicsmentioning
confidence: 96%